Attitudes of Pre-school Teachers towards Movement Education - Majid Al-Busafi; Kashef Zayed; Badriya Al Haddabi (Sultan Qaboos University, 2016)
Educators' attitudes have drawn attention of researchers worldwide, where numerous studies have been conducted to explore the factors that influence educators' attitudes toward educational topics in order to understand them and direct them in ways that contribute to the enhancement of the educational practices. In this study, we aimed to identify attitudes of early childhood educators in the Sultanate of Oman towards movement education, and to investigate the differences in attitudes according to nationality and qualification. The sample of this study consisted of 201 pre-school female educators in the Sultanate of Oman. The participants responded to Attitudes towards Movement Education Scale, which consisted of three dimensions (emotional, cognitive and behavioral). This scale was designed and modified for the purpose of this study. The results of this study revealed that the participants' attitudes towards movement education were positive in general. The emotional dimension ranked first (87.7%), followed by the cognitive (82.6%) and behavioral dimensions (78.8%). The results also showed that there were differences in attitudes towards movement education due to educators' nationality and educational levels.